Techniques to Achieve Stretchable Photovoltaic Devices from Physically Non‐Stretchable Devices through Chemical Thinning and Stress‐Releasing Adhesive. Issue 18 (30th June 2022) - Niu, Jing; Zhao, Yicong; Li, Mengwei; Xiang, Hongbiao; Xia, Zhiqiang; Ren, Miaoning; Gao, Peng; Huang, Xian
Abstract: Integration of photovoltaic devices on the deformable surfaces of plants and animals is challenging, as most of the photovoltaic devices possess no stretchability which severely restricts the underneath deformable substrates and causes potential delamination of the devices from the substrates due to large shear stress. Here, techniques to achieve stretchable photovoltaic devices through chemically thinning flexible solar cells and intermediate hard–soft transition layers are proposed. The resulting photovoltaic devices are only 25 µm in thickness with a radius of curvature of 1 mm, offering excellent adaptability to leaves and many curved surfaces. The intermediate layer that is based on silicone adhesive with low modulus provides an interface between non‐stretchable photovoltaic devices and deformable substrates, resulting in a stretchability of the overall structures larger than 140%. Key parameters of the photovoltaic device such as open‐circuit voltage, short circuit current, fill factor, and conversion efficiency indicate the excellent performance of thinned devices. Potential applications of ultra‐thin photovoltaic devices in energy harvesting and light intensity sensing on stretchable substrates are demonstrated, suggesting the practical use of the devices in constructing stretchable self‐powered wearable systems for agriculture and healthcare monitoring. Abstract : Techniques to achieve stretchable photovoltaic devices are presented. The resulting device can withstand more than 140% stretching and adapt to curved surfaces with small radii of curvature. The devices that have been demonstrated to conduct power harvesting and light intensity sensing on plants, may inspire rapid conversion of non‐stretchable electronics into ultra‐stretchable flexible electronics.